A methodological approach - Bragança, L. (2005)
The building sector plays a major role in the sustainable development. It is responsible for a major part of the raw materials extraction, energy consumption, waste production and it is the centre of the human life: the major part of the human life is spent inside a building. Nowadays, the society is making an effort regarding environmental protection and building ambient quality and a greater attention is being given to pollution control, energy efficiency, proper waste disposal, heritage preservation, social integration, indoor ambient quality, etc. This paper presents a methodology for the comparative sustainability assessment of construction solutions. This first methodological approach allows the users to define and qualify the indicators that are related to the requirements of the assessment and the proprieties of building solution. With this methodology is possible to consider different alternatives for the buildings elements, aiming the selection of the most sustainable solution. At the end of this paper, the methodology will be applied to some conventional and non-conventional floors construction solutions in order to find, inside the sample, the most sustainable solution.